Multicentre international trial of laparoscopic lavage for Hinchey III acute diverticulitis (LLO Study). Issue 13 (14th July 2018) - Binda, G A; Bonino, M A; Siri, G; Di Saverio, S; Rossi, G; Nascimbeni, R; Sorrentino, M; Arezzo, A; Vettoretto, N; Cirocchi, R; Birindelli, A; Bertone, S; et al.
Abstract: Background: Laparoscopic lavage was proposed in the 1990s to treat purulent peritonitis in patients with perforated acute diverticulitis. Prospective randomized trials had mixed results. The aim of this study was to determine the success rate of laparoscopic lavage in sepsis control and to identify a group of patients that could potentially benefit from this treatment. Methods: This retrospective multicentre international study included consecutive patients from 24 centres who underwent laparoscopic lavage from 2005 to 2015. Results: A total of 404 patients were included, 231 of whom had Hinchey III acute diverticulitis. Sepsis control was achieved in 172 patients (74·5 per cent), and was associated with lower Mannheim Peritonitis Index score and ASA grade, no evidence of free perforation, absence of extensive adhesiolysis and previous episodes of diverticulitis. The operation was immediately converted to open surgery in 19 patients. Among 212 patients who underwent laparoscopic lavage, the morbidity rate was 33·0 per cent; the reoperation rate was 13·7 per cent and the 30-day mortality rate 1·9 per cent. Twenty-one patients required readmission for early complications, of whom 11 underwent further surgery and one died. Of the 172 patients discharged uneventfully after laparoscopic lavage, a recurrent episode of acute diverticulitis was registered in 46 (26·7 per cent), at a mean of 11 (range 2–108) months. Relapse was associated with younger age, female sex and previous episodes of acute diverticulitis. Conclusion: Laparoscopic lavage showed a high rate of successful sepsis control in selected patients with perforated Hinchey III acute diverticulitis affected by peritonitis, with low rates of operative mortality, reoperation and stoma formation. Abstract : Successful in the majority